Environmental Strategies to Promote Food Intake in Older Adults: A Narrative Review. Issue 2 (2nd April 2016) - Stroebele-Benschop, Nanette; Depa, Julia; de Castro, John M.
ABSTRACT: Aging is often accompanied by lower intakes of food energy and consequent negative effects on health. To some extent this is due to declines in physiological ability, including the sensory responsiveness to regulate food intake. Fortunately, environmental factors may still influence food intake in older adults. Factors such as social facilitation, modeling, and nutrition knowledge and skills have been shown to stimulate their food intake. While environmental factors such as the eating location, portion size, food presentation, and labeling are known to influence eating behavior, their effectiveness in stimulating food intake in older persons is not well delineated. It is suggested that improving the environmental stimuli that promote food intake is a viable strategy to overcome age-related declines in nutrient intakes. This strategy is so promising that further research is warranted.